Qualitative evaluation of an educational intervention to reduce medicolegal risks for medical doctors experiencing significantly more cases than their peers in the UK and Ireland. Issue 4 (20th April 2018) - Jolly, John; Bowie, Paul; Price, Julie; Mason, Matt; Dinwoodie, Mark
Abstract : Objectives: The Medical Protection Society (MPS) is a leading protection organisation for healthcare professionals worldwide. In the UK and Ireland, a small minority of MPS members experience significantly more medicolegal cases than their peers and are invited to participate in a risk education (RE) remediation process. To understand more about this educational intervention, we sought to explore participating doctors' views of their experiences of this process and identify self-reported performance improvements and what elements of the intervention could be improved. Design: Qualitative semistructured telephone interviews with a convenience sample of doctors with significantly more medicolegal cases than their peers identified by MPS. Setting: UK and Ireland MPS members. Participants: A convenience sample of 20 general medical practitioners and hospital specialists from a total of 79 who completed the RE process (25.3% response rate), with a particular focus on the Member Risk Review programme, between November 2013 and October 2015. Results: 19 participants were male and 16 were based in general medical (office) practice. Three key themes were generated: personal and professional impacts and actions (eg, member has taken action to reduce clinical workload); comprehension and validity of RE interventions (eg, risks were related to wider patient management); and feedback and proposals (eg, the supportive nature of the educational interventions should be clear from the start). A number of recommendations were made by participants to improve the RE process and enhance the educational experience. Conclusions: The RE process was largely valued by participants with many reporting that participation led to some positive professional behaviour changes and improvements in practice processes and personal well-being.